Charles Earl family papers - Earl, Charles, 1836-1898.; Earl, Charles, 1836-1898.; Earl, Charles, 1869-1943.
Correspondence, family papers, military records, financial records, newspaper clippings, printed matter, photographs, and other papers of the Earl family. Primarily the papers of Charles Earl and his son, Charles Earl, Jr. Includes genealogical material of the Earl and Rogers families; estate papers of Sir Frederick W.A. Bruce and of Richard Bickerton Pemell Lyons, Earl Lyons; and a narrative of travels in China to the Great Wall of China and the Ming Tombs in 1863. Correspondents include Thomas Charles Bruce, Jane Cornelia Livermore Burlingame, George B. Cortelyou, and Oscar Straus.
Photocopies, in part.
Earl family members including Charles Earl, Sr., private secretary to Sir Frederick W.A. Bruce, British envoy to China and the United States, and Charles Earl, Jr., lawyer and public official.
Collection material in English.
Keywords: Bruce, Frederick W. A. -- Sir, -- 1814-1867 -- Estate; Bruce, Thomas Charles, -- 1825-1890 -- Correspondence; Burlingame, Jane Cornelia Livermore -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Lyons, Richard Bickerton Pemell Lyons, -- Earl, -- 1817-1887 -- Estate; Straus, Oscar, -- 1870-1954 -- Correspondence; Earl family; Rogers family; China -- Description and travel; Great Wall of China (China); Ming Tombs (China)